Introducing the NHS Evidence specialist collections - O'Brien, E; Bastin, E (2010)
Launched in April 2009 following the recommendations of the Darzi report1, NHS Evidence (http://www.evidence.nhs.uk) provides access to high quality, freely available health and social care information via a simple search function. The 34 NHS Evidence specialist collections were originally part of the National Library for Health. They have remained on the same platform, with results from the collections viewable via the NHS Evidence search. Release 4 of NHS Evidence, due Spring 2011, will see the technical integration of the Specialist Collections in to the main search portal. This will provide users with a seamless experience, where previously they had to visit a separate URL, and will enhance the results in NHS Evidence. Furthermore, a new management model for the Specialist Collections will be introduced. The new model consists of “evidence hubs” which will see greater collocation of currently geographically dispersed staff. This will lead to a greater consistency in output, resulting in an overall improvement in the quality and reliability of content. Annual Evidence Updates will increase in quantity and frequency thanks to the increased efficiency achieved.